PERANAN DEWAN PERWAKILAN RAKYAT DAERAH DALAM PEMBENTUKAN PERATURAN DAERAH KABUPATEN LUWU TIMUR - Anthon Sattu Pabesak; Yoseph Pasolang (LPPM Universitas Ekasakti, 2022)
Abstract: In responding to the task of the DPRD of east Luwu Regency whice is a vehicle for democracy in the region and is closely related to the ability to accmmodate and formulate the aspiration of the people, which is the right of initiative in the formation of regional regulations. Abstrak: Dalam menyikapi tugas DPRD Kabupaten Luwu Timur yang merupakan wahana demokrasi di daerah dan bertautan erat dengan kemampuan dalam mengakomodir dan merumuskan aspirasi rakyatnya yang merupakan hak inisiatif dalam pembentukan peraturan daerah.